Luz, câmera e likes: o trabalho dos youtubers nas mídias digitais - Denari, Giulianna Bueno (2021)
This thesis aims to comprehend the work processes of content creators for digital platforms, known as YouTubers. The study of digital labor brings forth new possibilities for understanding occupational dynamics and interactions among workers, large companies, and users. Regulations stemming from algorithms, the assignment of responsibilities to workers in managing their time, space, type, and volume of work, complicate the discourses surrounding personal entrepreneurship. YouTube is a digital platform that offers resources for users to create and share video content. For companies, the platform sells advertising space and, primarily, the potential for reach through a massive audience. The central innovation of YouTube lies in the customization of consumed content. Moreover, users themselves not only consume but also create and share content on the platform, enabling deeper identification with their influencers. The guidelines set by the platform dictate the rhythms and work processes, demanding continuous adaptation from YouTubers to ensure the profitability of their endeavors. The work process of YouTubers transcends mere video elaboration and recording; it also involves forming partnerships, bureaucratic management, and the pursuit of expanding their image. With growth in numbers and relevance, YouTubers evolve into a sort of brand, needing to establish connections with other brands through partnerships. The optimistic view of an unpretentious and enjoyable occupation is questioned in the face of exhaustion that arises from the constant pursuit of staying "on top." The research development occurred in two stages and employed a variety of resources. Through online contacts, semi-structured interviews were conducted with YouTubers. Simultaneously, four channels were selected for systematic monitoring of all content produced by and about them. The records were documented in a field notebook, allowing for a reconstruction of their work trajectories. Additionally, secondary quantitative data on income and audience projection were used to comprehend the dynamics outlined by algorithms. The research hypothesizes the fundamental role that YouTubers play in redefining the dynamics of work in digital platforms. YouTubers can be understood as self-entrepreneurs; however, this presumed autonomy is influenced by the actions of the platform's algorithms and the complexity of the digital market. Through this investigation, we aim to examine how YouTubers navigate a landscape marked by dualities and how their practices both shape and are shaped by them. Our research seeks to contribute to a broader understanding of contemporary transformations in the world of work.